Instalação: espaço e tempo - Luciana Bosco e Silva (2011)
The research Installation: space and time, its a historical and critical reflection about the different aspects of Installation Art; its ephemeral and mutant characteristics at each different exhibition, and with that it´s particularities as a piece that it´s experimented on specific space and time. To question the relationship of space-time on Installation Art, these work will use Installation that are ephemeral by its nature, as ones that are made by perceives materials and also the ones that are made as temporary pieces, as well in situ Installation Art and its particularities with the space in which the piece is installed. This issues of space and time are seen here on indoor Installation pieces as well on outdoor pieces, in which the space itself is part of the piece, as are the cases on Land Art as well on Urban Intervention. This work also question the validation of an exposition of this way of art, out of the criterion chosen by the artist at the moment of its creation, accentuating the subject of its space and timing and the reproduction of the art work at any new exhibition. The reflection that this work intends to do, its based on the dialogue between the art object and the observer, witch is, in the case of Installation art, an active agent in the complement of the work itself, where the joy of the pure essence of the work its, in many cases, absolutely necessary for the real existence of it. The Installation Art: space and time, is therefore, the result of a research that does a reflection about how important emptiness, time and space are to the real meaning of Installation Art.